The Saccharomyces Ty5 retrotransposon family is associated with origins of DNA replication at the telomeres and the silent mating locus HMR. - Zou, S (1995)
We have characterized the genomic organization of the Ty5 retrotransposons among diverse strains of Saccharomyces cerevisiae and the related species Saccharomyces paradoxus. The S. cerevisiae strain S288C (or its derivatives) carries eight Ty5 insertions. Six of these are located near the telomeres, and five are found within 500 bp of autonomously replicating sequences present in the type X subtelomeric repeat. The remaining two S. cerevisiae elements are adjacent to the silent mating locus HMR and are located within 500 bp of the origin of replication present in the transcriptional silencer HMR-E. Although the S. cerevisiae Ty5 elements no longer appear capable of transposition, some strains of S. paradoxus have numerous Ty5 insertions, suggesting that transposition is occurring in this species. Most of these elements are adjacent to type X telomeric repeats, and regions flanking four of five characterized S. paradoxus insertions carry autonomously replicating sequences. The genomic organization of the Ty5 elements is in marked contrast to the other S. cerevisiae retrotransposon families (Ty1-4), which are typically located within 500 bp of tRNA genes. For Ty3, this association reflects an interaction between Ty3 and the RNA polymerase III transcription complex, which appears to direct integration [Chalker, D. L. & Sandmeyer, S. B. (1992) Genes Dev. 6, 117-128]. By analogy to Ty3, we predict that Ty5 target choice is specified by interactions with factors present at both the telomeres and HMR that are involved in DNA replication, transcription silencing, or the maintenance of the unique chromatin structure at these sites.